Understanding the role of iron in the magnetism of Fe doped ZnO nanoparticles. Issue 23 (21st June 2015) - Beltrán, J. J.; Barrero, C. A.; Punnoose, A.
<x xml:space="preserve">Abstract</x> Fe does not contribute directly to ferromagnetic signals, but promotes the formation of defects which are considered as main sources.